IMPROVING STUDENTS’ VOCABULARY LEARNING OUTCOME BY USING FREERICE - Nabila, Afanin; Daulay, Sholihatul Hamidah; Dewi, Utami (Universitas PGRI Sumatera Barat, 2023)
Language's vocabulary plays a significant part in the process of communication, both verbally and in writing. Both the daily world and the world of education need it. This study was carried out based on the problems of students that have difficulties in memorizing vocabularies. The purpose of this study was to investigate how Freerice as a learning medium can improve the students’ vocabulary learning outcome at SMP N 4 Medan at the seventh grader in academic year of 2022/2023. The research was conducted with using a mixed-method. Meaning that the data collected quantitatively then will be explained qualitatively. The data instruments were questionnaires and tests. The participants were all students from class VII-2, and they are 30 students in total. Which the 25 of them did the questionnaire and 5 of them did the test. The questionnaires are 10 items and were constructed based on Likert Scale. The questions are close-ended type. Meanwhile, the tests were gathered quantitatively and will be done twice before/after the use of Freerice to the students’ vocabulary learning outcome. The result showed that the students’ learning outcome is improved using Freerice as a medium to learn vocabulary.